First-principles investigation on structural, electronic, and optical properties of (Cd1-xZnx)3As2 - Yu Deng; Xun Ge; Rongxiu Feng; Yunye Liang; Xiaohao Zhou (Next Materials)
This work focus on the investigation of the structural, electronic properties, and optical properties of the alloy (Cd1-xZnx)3As2 using first-principles. The first-principles, couple with the special quasi-random structure (SQS) method, are used to predict the stable structure of the variable bandgap alloy (Cd1-xZnx)3As2, on the basis of Cd3As2 and Zn3As2. Calculations show that the band gap width increases with the increasing of the compositions (x) in (Cd1-xZnx)3As2 and satisfies a certain linear relationship. Investigation on the density of states for (Cd1-xZnx)3As2 revealed a significant change in the contribution near the Fermi surface as the composition of Zn (x) increases. In addition, the electronic effective mass changes with different compositions (x), but the overall effective mass remains consistently low level (< 0.2 m0), which favors carrier diffusion in the crystal. Calculations on the optical properties (dielectric function, absorption coefficient) of (Cd1-xZnx)3As2 show that it behaves well in the near infrared and far infrared. For example, in the around 1.24 μm, the intrinsic absorption coefficient could up to 5.8×104 cm−1. The results of this article provide valuable insights into the superior properties of (Cd1-xZnx)3As2 alloys, which can guide structure design and optimization for high-performance photodetectors.